Effect of fly ash as partial cement replacement on workability and compressive strength of palm oil clinker lightweight concrete - Norhaiza, Ghazali; Khairunisa, Muthusamy; Rahimah, Embong; I. S., A. Rahim; N. F., Muhamad Razali; Fadzil, Mat Yahaya; Nur Farhayu, Ariffin; Saffuan, Wan Ahmad (IOP Publishing Ltd., 2021)
Environmental pollution caused by waste disposal namely palm oil clinker and fly ash from palm oil industry and coal power plant respectively needs to be resolved. The present investigation explores the influence of fly ash (FA) as partial cement replacement on workability, compressive strength and flexural strength of palm oil clinker lightweight aggregate concrete. A total of five types of mixes consisting 0%, 10%, 20%, 30% and 40% FA as cement replacement were used. All specimens were subjected to curing process by immersing it in water until the testing date. Concrete specimens were subjected to compressive strength and flexural strength test at 7 and 28 days. Incorporation of fly ash as partial cement replacement influences the fresh and hardened properties of this lightweight aggregate concrete. This novel finding shows that integration of up to 20% FA increases workability and contribute to strength enhancement of palm oil clinker lightweight aggregate concrete.